Readiness for transition and health‐care satisfaction in adolescents with complex medical conditions. (16th April 2019) - Haarbauer‐Krupa, Juliet; Alexander, Nneka Morris; Mee, Laura; Johnson, Alcuin; Wise, Justin; Arora Gupta, Nitika; Schechter, Michael S.; Wasilewski‐Masker, Karen; Gilleland Marchak, Jordan
Abstract: Background: The purpose of this study is to examine contributions to patient perceptions of transition readiness and satisfaction with care amongst adolescents and young adults (AYAs) with complex health conditions engaging in paediatric care. Methods: Participants included 94 patients aged 14–20 years ( M  = 16.41, SD  = 1.56) with cystic fibrosis ( n  = 31), sickle cell disease ( n  = 27), and solid organ transplants ( n  = 36). Participants completed self‐report questionnaires and medical providers completed measures of their medication regimen complexity. One‐way analysis of variance compared differences between disease groups on study variables. Pearson product–moment correlation coefficients and linear regression models evaluated factors associated with AYA reported transition readiness and satisfaction with health care. Results: There were no significant differences between disease groups on patient‐reported transition readiness, barriers to medication adherence, health care self‐management, or satisfaction. Patient age, self‐reported health‐care responsibility, medication barriers, and academic performance predicted a large portion of the variance in AYA perceptions of transition readiness (R 2  = 0.27, F (4, 83) = 7.74, p  < 0.001, Cohen's f2 = 0.37). Patient gender, self‐reported health‐care responsibility, and medication barriers predicted a medium portion of the variance in AYA satisfaction with health care (R 2  = 0.23, F (3, 88) = 8.56, p  < 0.001, Cohen's f2 = 0.30). Conclusions: Patient perceptions of health care self‐management and barriers to medication adherence are important predictors of readiness for transition and satisfaction with care. Considering a holistic approach that includes these factors allows for improved understanding of individual needs for transition interventions that can improve adult outcomes for individuals with complex health conditions.